Identification and Characterization of Immunoglobulin T Heavy Chain in Large Yellow Croaker (Larimichthys crocea) - Yan Teng; Qiuling Fu; Yuanzhen Tan; Yangyang Ding; Yang Ding; Xinhua Chen (Fishes, 2022)
Three immunoglobulin (Ig) isotypes have been identified in teleosts, IgM, IgD, and IgT or IgZ. IgT, a new teleost Ig isotype, plays a vital role in mucosal immunity. However, information on molecular and functional characteristics of fish IgT is still limited. In this study, an IgT heavy chain (LcIgT) gene was cloned and characterized in large yellow croaker (Larimichthys crocea). Complete cDNA of LcIgT was 1930 bp in length, encoding a protein of 554 amino acids. The deduced LcIgT contains a VH region and only three CH regions (CH1, CH2, CH4), but no transmembrane region was predicted. Phylogenetic analysis showed that IgT heavy chain sequences from all fish species are grouped together. Homology comparison showed that LcIgT shares the highest amino acid identity of 58.73% with IgT heavy chain in Scophthalmus maximus. The VH domain of LcIgT has the highest identity of 72.50% with that of Scophthalmus maximus IgT. Relatively, each constant domain of LcIgT exhibits the highest amino acid identity with that of IgT in Oreochromis niloticus (67.61% identity for CH1, 61.11% identity for CH2, and 63.74% identity for CH4). LcIgT was constitutively expressed in various tissues tested, with the highest levels in mucosa-associated tissues such as gills and skin. After Cryptocaryon irritans infection, the mRNA levels of LcIgT were significantly up-regulated in the spleen (3.27-fold) at 4 d, in the head kidney (3.98-fold) and skin (2.11-fold) at 7 d, and in gills (4.45-fold) at 14 d. The protein levels in these detected tissues were all significantly up-regulated; the peak of its up-regulation was 6.33-fold at 28d in gills, 3.44-fold at 7d in skin, and 3.72-fold at 14d in spleen. These results showed that IgT response could be simultaneously induced in both systemic and mucosal tissues after parasitic infection and that IgT may be involved in systemic immunity and mucosal immunity against parasitic infection.